Antidepressant-Like Effects of Coumaroylspermidine Extract From Safflower Injection Residues - Li, Shifei; Li, Ting; Jin, Yufang; Qin, Xuemei; Tian, Junsheng; Zhang, Liwei (Frontiers in Pharmacology, 2020)
In this study, a total coumaroylspermidine extract (CSE) including four coumaroylspermidine compounds was prepared from Safflower Injection (a prescription medicine of Traditional Chinese Medicine) residues for the first time. The total content of the four coumaroylspermidine compounds was determined to 58±3% by the HPLC technology. Moreover, the anti-depressant effect of CSE was evaluated by the chronic unpredictable mild stress rats (CUMS). Results suggested that CSE exhibited a significant anti-depressant effect in the sucrose preference test, open filed test and force swimming test. In the mechanism study, CSE was found to inhibit the increased levels of corticosterone and the decreased levels of 5-hydroxytryptamine, dopamine, noradrenaline. Meanwhile, ten endogenous metabolites and four metabolic pathways were altered and influenced after CSE treatment in the metabolic profiling. Thus, this study not only provided a way to utilize the Safflower Injection residues, but throw a light on the adoption of CSE as an adjuvant drug for depression in future.